Implementation of Green Sea Turtle Organism Level Biomimicry Principles in Sustainable Glamping Resort Design - Aprilio Cardiola; Veronika Widi Prabawasari (Universitas Muhammadiyah Surakarta, 2026)
The increase in tourist accommodation needs, particularly in Tanjung Benoa, Bali, has led to the development of unique concepts such as glamping resorts. However, this development must address the crucial issue of Green Sea Turtle (Chelonia mydas) conservation, as Tanjung Benoa is a natural habitat for this endangered species. This research aims to solve the architectural design problem of a glamping resort in an environment with conservation issues by implementing the organism-level biomimicry approach on the Green Sea Turtle. This approach utilizes nature-tested solutions to develop a sustainable design. The study employs a design exploration method by substituting the five organism-level biomimicry variables (form, material, construction, process, and function) with the biological characteristics of the Green Sea Turtle. These variables are analyzed based on relevant architectural theories. The result shows a design concept for three glamping unit types that reflects the turtle's form and material composition, an elevated structure adapted from the turtle's skeleton, and spatial and utility planning that supports the turtle's life cycle and coastal ecosystem conservation. This design demonstrates that biomimicry principles provide sustainable tourism solutions by integrating five organism-level variables into technical architectural elements that minimize habitat disruption, preserve nesting grounds, and synchronize the resort's operational cycles with the natural ecosystem of the Green Sea Turtle.